The Role of Matrix Metalloproteinases in Development, Repair, and Destruction of the Lungs - Hendrix, Amanda Y; Kheradmand, Farrah (Progress in molecular biology and translational science, 2017)
Normal gas exchange after birth requires functional lung alveolar units that are lined with epithelial cells, parts of which are intricately fused with microvascular capillaries. A significant phase of alveolar lung development occurs in the perinatal period, continues throughout early stages in life, and requires activation of matrix-remodeling enzymes. Failure to achieve an optimum number of alveoli during lung maturation can cause several untoward medical consequences including disabling obstructive and/or restrictive lung diseases that limit physiological endurance and increase mortality. Several members of the matrix metalloproteinase (MMP) family are critical in lung remodeling before and after birth; however, their resurgence in response to environmental factors, infection, and injury can also compromise lung function. Therefore, temporal expression, regulation, and function of MMPs play key roles in developing and maintaining adequate oxygenation under steady state, as well as in diseased conditions. Broadly, with the exception of MMP2 and MMP14, most deletional mutations of MMPs fail to perturb lung development; however, their individual absence can alter the pathophysiology of respiratory diseases. Specifically, under stressed conditions such as acute respiratory infection and allergic inflammation, MMP2 and MMP9 can play a protective role through bacterial clearance and production of chemotactic gradient, while loss of MMP12 can protect mice from smoke-induced lung disease. Therefore, better understanding of the expression and function of MMPs under normal lung development and their resurgence in response respiratory diseases could provide new therapeutic options in the future.